RANCANG BANGUN INSTRUMENTASI LOAD CELL STRAIN GAUGE HALF BRIDGE PADA DYNAMOMETER PRONY BRAKE DENGAN SISTEM MONITORING LCD 16X4 DISPLAY BERBASIS MIKROKONTROLER ARDUINO - Abdul Majid; Althesa Androva; Agus Mukhtar (Cross-border, 2023)
Prony Brake is one of the absorption type dynamometers because its work depends on adjusting the pulling torque, converting mechanical energy into heat. This tool will convert the output power of the motor into heat energy due to friction between the rotor shaft and the clamps. This prony brake system has vertical and horizontal load torque settings to achieve the desired loading conditions. This research focuses on the use of the Load Cell sensor as a receiver for the Prony Brake braking power load. So the purpose of this research is to see the performance of the instrumentation on the circuit and sensor readings. In this study, we obtained a Prony Brake dynamometer using a Load Cell Strain Gauge based on the mass or load caused by braking power by displaying the value on the Arduino nano-based 16x4 LCD that the researchers designed was less than optimal in carrying out its function. And the results on the performance of the Load Cell Strain instrument The gauge is still not optimal, it is obtained that the error limit (Error) in the braking power of the tool against the target has an average of 2.76% according to the provisions of the error with an average of 2kg not more than 2%.